Financial Distress, Company Growth, Previous Year's Audit Opinion, and Going concern Audit Opinion (E-Jurnal Akuntansi, 2026)
An audit opinion concerning going concerns is issued when the auditor assesses that the auditee may face challenges in sustaining operational continuity. This research aims to empirically demonstrate the influence of financial distress, company growth, and the previous year's audit opinion on the issuance of going concern audit opinions. The study focuses on consumer cyclicals companies listed on the Indonesian Stock Exchange (IDX) from 2020 to 2022. Data for this period were analyzed using logistic regression. Purposive sampling was employed to select 62 enterprises, resulting in 186 observations for analysis. The findings reveal that financial distress has a negative impact, while the previous year's audit opinion exerts a positive influence on the likelihood of issuing a going concern audit opinion. In contrast, company growth was found to have no significant effect.
Keywords: Going concern; Financial Distress; Company Growth; Previous Year’s Audit Opinion